(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The purpose of the research is to know the role of the external auditor in strengthening the principle of disclosure and transparency of the Iraqi private banks. The importance of the research is to highlight the role of the external auditor in applying the rules of disclosure and transparency in the financial statements of banks to be comprehensive and sufficient to meet the uses of all parties. The researcher used the documentary approach to complete the theoretical aspect and used the descriptive method (case study) to complete the practical aspect of the research. The preliminary data were collected in the field study through the questionnaire designed for this purpose. As well as the use of the Statistical Package for Social Sciences (SPSS) to process statistical data. The research concluded that the external auditor ensures that all the information and data in the financial statements are presented to be comprehensive and sufficient to meet the needs of all users. The research recommended some recommendations. The role and role of the external auditor in issuing financial statements To banks in particular and to economic companies in general, but must go beyond that to evaluate the performance so that it can make the right decisions and sound in a timely manner.